Fixed and mobile-bearing total ankle prostheses: Effect on tibial bone strain. (October 2017) - Terrier, Alexandre; Fernandes, Caroline Sieger; Guillemin, Maïka; Crevoisier, Xavier
Abstract: Background: Total ankle replacement is associated to a high revision rate. To improve implant survival, the potential advantage of prostheses with fixed bearing compared to mobile bearing is unclear. The objective of this study was to test the hypothesis that fixed and mobile bearing prostheses are associated with different biomechanical quantities typically associated to implant failure. Methods: With a validated finite element model, we compared three cases: a prosthesis with a fixed bearing, a prosthesis with a mobile bearing in a centered position, and a prosthesis with mobile bearing in an eccentric position. Both prostheses were obtained from the same manufacturer. They were tested on seven tibias with maximum axial compression force during walking. We tested the hypothesis that there was a difference of bone strain, bone-implant interfacial stress, and bone support between the three cases. We also evaluated, for the three cases, the correlations between bone support, bone strain and bone-implant interfacial stress. Findings: There were no statistically significant differences between the three cases. Overall, bone support was mainly trabecular, and less effective in the posterior side. Bone strain and bone-implant interfacial stress were strongly correlated to bone support. Interpretations: Even if slight differences are observed between fixed and mobile bearing, it is not enough to put forward the superiority of one of these implants regarding their reaction to axial compression. When associated to the published clinical results, our study provides no argument to warn surgeons against the use of two-components fixed bearing implants. Highlights: Finite element analysis of ankle arthroplasty to compare fixed and mobile insert No significant ( n = 7) differences in bone strain Strong correlation between bone strain and bone support